Electronic structure of two-dimensional In and Bi metal on BN nanosheets - Bo, Maolin (2021)
The electronic structures of two-dimensional (2D) indium (In) and bismuth (Bi) metal on BN nanosheets are systematically studied using hybrid density functional theory (DFT). We found that 2D In and Bi metal effectively modulate the band gap of a BN nanosheet. We also found that the indirect band gap of the 2D In and Bi metal electronic structures are 0.70 and 0.09 eV, respectively. This modulation originates from the charge transfer between the 2D metal and BN nanosheet interfaces, as well as from the electron redistribution of the In/BN and Bi/BN heterojunctions of the s and p orbitals. Our results provide an insight into 2D In/BN and Bi/BN heterojunctions, which should be useful in the design of 2D In and Bi metal-semiconductor-based devices.